Growth control and enrichment of Si crystals from Si-Sn melt by directional solidification. (December 2018) - Ren, Yongsheng; Wang, Hongpo; Morita, Kazuki
Abstract: The growth control and enrichment of Si crystals using Si-50 at.% Sn melts via upwards and downwards directional solidification at various moving rates was investigated. As expected, a large area of quasi-bulk Si (98.6% enrichment percentage) was successfully obtained at the 0.01 mm/min upwards moving rate. Moreover, after HCl leaching, the residual at.% of Sn in the enriched Si area was easily reduced to the 0.00132–0.00163 range, which was almost the same as that for the solid solubility of Sn in Si. Furthermore, a model was established to explain the crystal growth process and enrichment mechanism during directional solidification. In conclusion, we chose the upwards moving direction for the follow-up experiments, which solved the most critical first step of using Si-based alloy solvent refining to produce solar grade Si. Highlights: Solved the most critical first step of using Si-Sn solvent refining to produce SOG-Si. A model to explain the Si crystal growth and enrichment mechanism was established. Large area of quasi-bulk Si with 98.6% Si enrichment was successfully obtained. Residual at.% of Sn in enriched Si can be easily reduced to 0.00132–0.00163. Residual Sn content is similar to the solid solubility of Sn in Si.